Leaf development and growth of selected sugarcane clones in a subtropical environment - Streck, Nereu Augusto; Hanauer, Joana Graciela; Gabriel, Luana Fernandes; Buske, Taise Cristine; Langner, Josana Andréia (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to compare phyllochron and leaf area on individual stalks of selected sugarcane (Saccharum officinarum) clones grown in a subtropical environment. A two-year field experiment was carried out in Santa Maria, RS, Brazil, during the 2007/2008 and 2008/2009 growing seasons. Three sugarcane clones were used: IAC 822045 (early), SP 711406 (median) and CB 4176 (late), in a complete randomized block design, with four replications. Expanded leaf and total leaf (tips) number were determined, and expanded leaf area was measured. The phyllochron (ºC day leaf-1) based on expanded and tip leaf number was stimated, using 10ºC as base temperature. Allometric relationships between individual area and number of expanded leaves were fitted. Phyllochron was analysed as a four-factor experiment: clone, growing season, phyllochron phase, and phyllochron type. The early clone had the greatest potential for growing in a subtropical climate because of higher leaf output and leaf area.